2023
DOI: 10.1891/rtnp-2022-0146
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Long COVID Symptoms: An Evidence-Based Standardized Mapping Study With the Omaha System

Abstract: Background:In COVID-19 survivors, symptom burden is a significant and multifaceted personal and societal challenge. The Omaha system is a standardized terminology used by researchers and clinicians for documentation and analysis of meaningful data for whole-person health. Given the urgent need for a standardized symptom checklist specific to the long COVID population, the purpose of the present study was to identify long COVID symptoms from the published literature (native symptoms) and map those to the Omaha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
1
0
2
Order By: Relevance
“…В изученной популяции ожирением страдали 42% при ИМТ: M ± SD (кг/м 2 ) = 28 ± 5 (27)(28)(29). Из них ожирение: ■ 1-й степени -30%, ■ 2-й степени -8%, ■ 3-й степени -2%.…”
Section: взаимосвязь синдрома усталости и ожиренияunclassified
See 1 more Smart Citation
“…В изученной популяции ожирением страдали 42% при ИМТ: M ± SD (кг/м 2 ) = 28 ± 5 (27)(28)(29). Из них ожирение: ■ 1-й степени -30%, ■ 2-й степени -8%, ■ 3-й степени -2%.…”
Section: взаимосвязь синдрома усталости и ожиренияunclassified
“…В литературе описано более 200 симптомов, выявляемых после перенесенной новой коронавирусной инфекции [28], при этом усталость может сочетаться с дыхательными расстройствами (abnormal breathing) [29]. Наши результаты так же демонстрируют связь синдрома усталости с другими симптомами «долгого COVID-19», в том числе с одышкой.…”
Section: Covid-19unclassified
“…Some of the common mental health issues that COVID-19 survivors have reported include post-traumatic stress disorder, depression, and anxiety disorders [1,9]. Overall, reviews have shown that long covid affects a variety of symptoms, including mental health, gastrointestinal, cardiopulmonary, and neurological, without a clear etiological explanation [10,11]. However, with SARS-CoV-2 being a novel virus, the long-term effects of COVID-19 on survivors are still being uncovered [1].…”
mentioning
confidence: 99%